Plan de Negocio para el Montaje de Una Empresa Procesadora de Yogurt natural a base de pulpa de Mango en la ciudad de Santa Marta (2021)
The Colombian Atlantic coast, specifically the city of Santa Marta, has a competitive advantage over other cities in the country regarding the consumption of mango as a tropical fruit, this fruit is found in a large number of gastronomic presentations and varied preparations in countless products. ranging from natural drinks to specialized haute cuisine dishes, they take advantage of all the nutritional benefits and other properties derived from it that could make it a highly accepted and popular culinary component. The central objective of this business model is based on the establishment of a technical feasibility study for the creation of a natural yogurt processing company based on mango pulp in the city of Santa Marta. commercial (market) recognition, a technical - operational recognition and a financial study, in this section the prospects of economic viability were evaluated connoting the main decision criteria: the Net Present Value - NPV and the Internal Rate of Return - IRR; This was done in order to determine the future potential of execution of the proposal, as well as its perspective of strategic development in operational matters. The methodological recognition scheme uses a quantitative-descriptive investigative technique. A survey instrument was designed based on evaluative criteria at the price level, acceptance attributes and unsatisfied needs among the target audience; The results obtained in each of the studies used, denote a high potential to implement this business model in the future.